I’ll tell you what I want, what I really, really want: Open Archaeology that is collaborative, participatory, public, and feminist - Kiddey, R (Taylor & Francis, 2020)
In this paper, my aim is to remake a powerful case for an open archaeology that is always collaborative, participatory, and public – but also feminist and activist. Drawing on more than 10 years’ experience as a community archaeologist I discuss some of the reasons why researchers who employ collaborative approaches to the past may be reluctant to publicly acknowledge the frictions which inevitably arise through their work. By unpacking some of the key concepts employed in these approaches, like ‘community’, ‘public’ and ‘collaboration’, I consider how we might define the limits of inclusivity and openness in the name of democracy. Furthermore, I identify some of the strategies and approaches to community archaeology, which I suggest are more likely to lead to beneficial or positive outcomes, proposing that an explicitly feminist lens will achieve the return to politics and provocation for which some scholars have recently called.